Enhanced thermoelectric performance of Bi0.5Sb1.5Te3 composites through potential barrier scattering at heterogeneous interfaces. (January 2021) - Dharmaiah, Peyala; Lee, Kap-Ho; Song, Sung Ho; Kim, Hyoung Seop; Hong, Soon-Jik
Graphical abstract: Highlights: Bi0.5 Sb1.5 Te3 composites with an in situ nanostructures were fabricated. Multiple-microstructure features had better energy filtering and phonon scattering. Intense phonon scattering at interfaces decreased lattice thermal conductivity. ZT = 1.35 at 350 K and conversion efficiency, ηmax = 8.74 % at ΔT =200 K were achieved for BST/2 wt% Zn4 Sb3 composites. Abstract: The inclusion of secondary phase in a matrix has been proven effective in diverse regimes of thermoelectric (TE) material research intended to attain high thermoelectric performance. Herein, we show that the introduction of semiconducting Zn4 Sb3 alloys into a Bi0.5 Sb1.5 Te3 matrix to form ZnTe nanophase in situ causes enhanced electrical conductivity and reduced thermal conductivity. This is due to increase in the carrier concentration and intensified phonon scattering at interface potentials. These simultaneously increased the power factor by 17 % and achieved a remarkable reduction (25 %) of lattice thermal conductivity at 350 K for BST/2 wt% Zn4 Sb3 composites. As a result, the largest value of ZT (1.35) was obtained at 350 K, which is 26 % higher than that of the Bi0.5 Sb1.5 Te3 matrix at the same temperature. Moreover, the maximum conversion efficiency was about 8.74 % at ΔT =200 K for BST/2 wt% Zn4 Sb3 composites, which is 25 % higher than that of a bare BST sample.